2021
DOI: 10.1109/access.2021.3069163
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Fisher Information of a Teleported State in Heisenberg XYZ Chain With Magnetic Field and Kaplan–Shekhtman–Entin-Wohlman–Aharony Interaction

Abstract: One of the teleportation versions is applied to convey an entangled two-qubit system via a class of a two-qubit XYZ Heisenberg chain model. At thermal equilibrium, the exact solution of the XYZ model with an external magnetic field and the Kaplan-Shekhtman-Entin-Wohlman-Aharony interaction (KSEWA-interaction) is proposed in X, and Z direction. The teleported quantum Fisher information is studied, where we estimate the weight parameter θ, temperature, and the strength parameter of KSEWAinteraction. It is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…and the KSEA interaction has been observed experimentally in the helimagnetic insulator Ba 2 CuGe 2 O 7 [69]. Its effect on entanglement [70][71][72], quantum discord [70,73,74], quantum Fisher information [74,75], as well as quantum consonance, uncertainty-induced nonlocality, and entropic uncertainty [76] has also been reported recently. Unlike these works, we investigate combined effects of the DM and KSEA interactions on ASC in the Heisenberg model.…”
Section: Introductionmentioning
confidence: 92%
“…and the KSEA interaction has been observed experimentally in the helimagnetic insulator Ba 2 CuGe 2 O 7 [69]. Its effect on entanglement [70][71][72], quantum discord [70,73,74], quantum Fisher information [74,75], as well as quantum consonance, uncertainty-induced nonlocality, and entropic uncertainty [76] has also been reported recently. Unlike these works, we investigate combined effects of the DM and KSEA interactions on ASC in the Heisenberg model.…”
Section: Introductionmentioning
confidence: 92%
“…[24][25][26][27][28][29][30][31] Through various Heisenberg spin chain models, and in the presence of Dzyaloshinskii-Moriya interactions, dipole-dipole interaction, and spin squeezing mechanisms, entanglement teleportation and fidelity are investigated. [32][33][34][35][36][37][38][39][40][41] On the other hand, the Bell theorem has been a step forward in quantum physics that demonstrates the limitations of the natural assumption of locality. [42] By using Bell inequalities, it is shown that there are certain correlations between particles that cannot be explained by classical physics but require the use of quantum physics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24–31 ] Through various Heisenberg spin chain models, and in the presence of Dzyaloshinskii–Moriya interactions, dipole–dipole interaction, and spin squeezing mechanisms, entanglement teleportation and fidelity are investigated. [ 32–41 ]…”
Section: Introductionmentioning
confidence: 99%
“…The non-classicality and the non-locality of two-qubit Werner state and two-qutrit under the effect of some classical noise environment have been discussed (Rahman et al 2022a, b). Some quantum correlations dynamics features of Bell nonlocality, entanglement and entropic uncertainty of Dzyaloshinskii-Moriya (DM), Kaplan-Shekhtman-Entin-Wohlman-Aharony(KSEA) interactions with external magnetic field, and intrinsic decoherence have obtained (Abd-Rabboul et al 2021;Hashem et al 2022;Essakhi et al 2022). The concurrence is a simple measure of entanglement that provides an analytic formula for the entanglement of formation (EoF) which is one of three widely studied measures of entanglement of a general bipartite system (Wootters 2001).…”
Section: Introductionmentioning
confidence: 99%